Surfaces of coastal biogenic structures: exploiting advanced digital design and fabrication strategies for the manufacturing of oyster reef and mussel bed surrogates - Hitzegrad, Jan; Brohmann, Leon; Herding, Friedrich; Pfennings, Kai; Jonischkies, Sven; Scharnbeck, Elisa; Mainka, Jeldrik; Mai, Inka; Windt, Christian; Kloft, Harald; Wehrmann, Achim; Lowke, Dirk; et al. (Frontiers in Marine Science, 2024)
Coastal biogenic structures, formed by ecosystem engineering species, often feature rough surfaces characterized by intricate topographies and highly three-dimensional reliefs. Their surfaces are shaped by waves and tidal currents and reciprocally influence the ambient hydrodynamics, reflecting an equilibrium. Despite their significance, the impact of these surfaces on the ambient hydrodynamics remains underexplored due to limited knowledge of accurately replicating their complex topographies in experimental setups. The recent advent of advanced digital manufacturing presents an efficient means to manufacture highly complex, three-dimensional surrogate models for experimental modeling. This work explores the accurate replication of rough coastal biogenic structures for experimental modeling on the examples of an oyster reef and a mussel bed, utilizing a flexible design methodology and, for the first time, particle bed 3D printing with Selective Cement Activation (SCA) as a fabrication and manufacturing method. A workflow is proposed, which includes an iterative surrogate model development based on in-situ topographical features, requirements of the experimental setup, and parameters of the particle bed 3D printer with SCA. The results demonstrate the effectiveness of the methodology in achieving highly accurate surrogate surfaces of complex coastal biogenic structures by validation against a set of topographical features relevant to hydraulic roughness. Particle bed 3D printing with SCA proved to be a suitable method to manufacture complex surrogate surfaces for experimental modeling, offering advantages such as independence of production time from surface complexity. However, challenges persist in achieving exact comparability between the manufactured surrogate surface and the real coastal biogenic structures, particularly for surfaces with very high complexity. Nonetheless, the manufactured generic surrogate surfaces enable detailed investigations into the influence of complex coastal biogenic structures on the ambient hydrodynamics, thereby enhancing the understanding of the processes governing wave energy dissipation attenuation, turbulence production, and vertical mixing – critical for efficient application as a nature-based solution on coastal protection or restoration efforts.